2021
DOI: 10.3892/etm.2021.10172
|View full text |Cite
|
Sign up to set email alerts
|

Effects of NSAIDs on pre‑osteoblast viability and osteogenic differentiation

Abstract: Non-steroidal anti-inflammatory drugs (NSAIDs) are widely used in the treatment of a variety of musculoskeletal conditions, injuries and after surgery for postoperative pain management. Their use has been associated with impaired bone healing, possibly due to a multifactorial function, which may include inhibition of osteoblast recruitment and differentiation. However, up to date, there is no consensus regarding the impact of NSAIDs on bone-healing. The aim of the current study was to investigate the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
(68 reference statements)
0
9
0
Order By: Relevance
“…It has also been reported that diclofenac inhibits BMP-7 which induces the differentiation, maturation and proliferation of osteoblasts from mesenchymal cells [ 26 ]. Recently reported data state that NSAIDs could demonstrate a negative effect on the bone healing process by down-regulating chondrogenesis and endochondral ossification [ 27 ], and that diclofenac has a negative impact on pre-osteoblast cell growth [ 17 ]. Bissinger et al [ 28 ] investigated the effect of diclofenac on fractures through a biomechanically, morphologically and by 3-dimensional microstructural analysis and reported an inhibiting effect on bone healing, but also additional changes which occurred in the microstructural bony network.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that diclofenac inhibits BMP-7 which induces the differentiation, maturation and proliferation of osteoblasts from mesenchymal cells [ 26 ]. Recently reported data state that NSAIDs could demonstrate a negative effect on the bone healing process by down-regulating chondrogenesis and endochondral ossification [ 27 ], and that diclofenac has a negative impact on pre-osteoblast cell growth [ 17 ]. Bissinger et al [ 28 ] investigated the effect of diclofenac on fractures through a biomechanically, morphologically and by 3-dimensional microstructural analysis and reported an inhibiting effect on bone healing, but also additional changes which occurred in the microstructural bony network.…”
Section: Discussionmentioning
confidence: 99%
“…The negative effect of diclofenac on bone healing may be attributed to its adverse effects, since it has been reported that diclofenac inhibits the proliferation and induces the apoptosis of human osteoblast cells [ 16 ]. Furthermore, on a cellular level, diclofenac may show a negative impact on pre-osteoblast cell growth [ 17 ]. However, recent studies have assumed the negative impact of diclofenac on bone metabolism to be subsidiary [ 18 ], while Cai et al [ 19 ] reported that diclofenac did not adversely affect the osseointegration of dental implants and bone healing in the calvaria, neither in the short nor the long term.…”
Section: Introductionmentioning
confidence: 99%
“…NSAIDs affect the osteoblastic cell cycle and cell death. A study showed that osteoblastic density was significantly decreased in groups exposed to diclofenac sodium compared to the control group (Hadjicharalambous et al 2021). The osteoclastic densities were found to be statistically significantly higher in a group exposed to diclofenac sodium than in the control group (p< 0.05).…”
Section: Discussionmentioning
confidence: 96%
“…Treatment of pre-osteoblasts with prednisolone resulted in increased ALP activity and decreased calcium deposition, decreased cell viability, and proliferation. It is already known that prednisolone can induce apoptosis of confluent osteoblasts [ 61 ]. While cortisol, a glucocorticoid hormone secreted in response to stress, can promote osteoblast differentiation at physiological concentrations [ 59 ], there are conflicting data on whether prednisolone can inhibit or increase the biological activity of osteoblasts and osteoclasts.…”
Section: Discussionmentioning
confidence: 99%
“…While cortisol, a glucocorticoid hormone secreted in response to stress, can promote osteoblast differentiation at physiological concentrations [ 59 ], there are conflicting data on whether prednisolone can inhibit or increase the biological activity of osteoblasts and osteoclasts. The effect seems to be concentration-dependent and depends on the developmental stage of the osteoblasts [ 61 63 ].…”
Section: Discussionmentioning
confidence: 99%